Implementasi Kebijakan Pemerintah dalam Pelestarian Cagar Budaya di Kabupaten Mojokerto (Studi pada kawasan cagar budaya Trowulan Kabupaten Mojokerto) - Prayogo, Bagus Unggul (Jurnal Administrasi Publik, 2013)
Bagus Unggul Prayogo, Suwondo, Minto Hadi Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, Malang E-mail: bagusunggulprayogo@yahoo.co.id     Abstract: The implementation of a government policy in the preservation of cultural heritage in the county of mojokerto areas ( study in the area of cultural heritage trowulan district mojokerto areas ). Related to the preservation of cultural heritage the Government follow through with the dikeluarkannyaUndang of the Republic of Indonesia No. 11 of 2010 about objects of cultural heritage that aims to protect Objects of cultural heritage as well as cultural heritage Sites which are located in Trowulan Mojokerto. The problems faced in business activities with the pelestariannyadalah excavation for the brick industry that made local people, these activities can threaten the integrity and keterselamatan Objects of cultural heritage are likely still buried. In addition there is the reluctance of the public to submit sites of cultural heritage that has been found to Ancient Relics Preservation Hall (BP3) as authorities because it does not get compensation. The research was conducted using a qualitative approach. The participation of Department of Youth, sports, culture and tourism in preservation in Trowulan also plays a very important, because here the task of Disporabudpar is promote the objects of cultural heritage is becoming a tourist attraction located in Mojokerto and could attract tourists to visit tourist places of cultural heritage objects. Constituents of the preservation of cultural heritage in Trowulan is a wealth of relics and sites of cultural heritage of Majapahit became an attraction for tourists to visit tourist places of cultural heritage located in Trowulan. As well as restricting factor is limitation of Fund budget, means of transportation due to the location of each site are far apart. Keywords: policy, cultural heritage, preservation.   Abstrak: Implementasi Kebijakan Pemerintah dalam Pelestarian Cagar Budaya di Kabupaten Mojokerto (Studi pada kawasan cagar budaya Trowulan Kabupaten Mojokerto). Terkait dengan pelestarian Cagar Budaya pemerintah menindaklanjuti dengan  dikeluarkannyaUndang-Undang Republik Indonesia No. 11 tahun 2010 tentang benda cagar budaya yang bertujuan untuk melindungi Benda Cagar Budaya serta Situs Cagar Budaya yang berada di Trowulan Kabupaten Mojokerto. Permasalahan yang dihadapi dalam usaha pelestariannyadalah dengan adanya kegiatan penggalian untuk industri batu bata yang dilakukan masyarakat setempat, kegiatan ini dapat mengancam keutuhan dan keterselamatan Benda Cagar Budaya yang kemungkinan masih terpendam. Selain itu ada keengganan dari masyarakat untuk menyerahkan situs cagar budaya yang telah ditemukan  kepada Balai Pelestarian Peninggalan Purbakala(BP3) selaku pihak berwenang karena tidak mendapatkan  kompensasi . Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif. Keikutsertaan Dinas Pemuda, Olahraga, Kebudayaan dan Pariwisata dalam pelestarian di Trowulan juga berperan sangat penting, karena disini tugas dari Disporabudpar  adalah mempromosikan benda cagar budaya menjadi obyek wisata yang berada di Kabupaten Mojokerto serta bisa menarik minat wisatawan untuk mengunjungi obyek wisata benda cagar budaya ini.  Faktor pendukung dari Pelestarian cagar budaya di Trowulan adalah dari kekayaan peninggalan dan situs cagar budaya Majapahit menjadi daya tarik bagi wisatawan untuk mengunjungi obyek wisata cagar budaya yang berada di Trowulan. Serta faktor penghambat adalah keterbatasan dana anggaran, sarana transportasi yang dikarenakan letak dari setiap situs saling berjauhan.   Kata kunci: Kebijakan, Cagar Budaya, Pelestarian.